The targets and indicators of Russia’s state public health program up to 2020 - O. B. Nechaeva; S. A. Sterlikov; N. B. Khurieva (Туберкулез и болезни лёгких)
Studying the targets and indicators of the Public Health Development Program up to 2020 concerning antituberculosis (anti-TB) care to the population may lead to the conclusion that they may be fulfilled in the Russian Federation as a whole. The difficulties in fulfilling the indicators are associated with the low level of tuberculosis detection in a number of subjects of the Russian Federation; the continuing development of the HIV epidemic; the inadequate development of bacteriological diagnosis of the drug sensitivity of the tuberculosis pathogen to anti-TB drugs; the nonuniform funding of anti-TB measures in the subjects of the Russian Federation – the annual financing per tuberculosis patient differs by 40 times, including that of the purchase of anti-TB drugs by 63 times. Having no federal financial assistance in purchasing reserve anti-TB drugs and consumables for microbiological tests, it is impossible to diagnose multidrug resistance and to cure patients with multidrug-resistant tuberculosis at the expense of the budgets of the Russian Federation’s subjects.